Cost-Effectiveness of Tislelizumab Versus Docetaxel for Previously Treated Advanced Non-Small-Cell Lung Cancer in China - Gong, Jinhong; Su, Dan; Shang, Jingjing; Xu, Shan; Tang, Lidan; Sun, Zhiqiang; Liu, Guangjun (Frontiers in Pharmacology, 2022)
Background: Tislelizumab, a new high-affinity programmed cell death protein-1 (PD-1) inhibitor, significantly prolonged the overall survival in pretreated non-small cell lung cancer (NSCLC). This study aimed to assess the cost-effectiveness of tislelizumab versus docetaxel for this population in China. Methods: A three-state partitioned survival model was developed to simulate advanced NSCLC. Efficacy and safety data were based on a global phase 3 clinical trial (RATIONALE 303). Utilities were mainly extracted from previously published resources. Costs were calculated from Chinese healthcare system perspective and only direct medical costs were covered. The main outcomes included total costs, life years (LYs), quality-adjusted life years (QALYs) and incremental cost effectiveness ratio (ICER). One-way and probabilistic sensitivity analyses were carried to test the uncertainty of the modelling results. Besides, several scenarios including tislelizumab price before negotiation, different docetaxel price calculation, 50-year time horizon and alternative utility values were assessed. Results: The model predicted an average gain of 0.62 LYs and 0.51 QALY for tislelizumab vs. Docetaxel, at the additional cost of 9, 219. The resulting ICER was 15033.92/LY and 18122.04 /QALY, both below the cost-effective threshold (CET) of 3 times gross domestic product (GDP) per capita in China. Sensitivity analyses showed the results to be robust over plausible range for majority of inputs. Utility of progression-free survival (PFS), followed by the price of tislelizumab, had the greatest impact on the ICER. The probability of being cost-effective for tislelizumab was 96.79% at the CET we set. Conclusions: Tislelizumab improves survival, increases QALYs and can be considered as a cost-effective option at current price compared with docetaxel for pretreated advanced NSCLC in China.